Insulin allergy manifesting soon after COVID‐19 vaccination (BNT162b2). Issue 3 (23rd December 2022) - Komamura, Hiroshi; Kawana, Yohei; Imai, Junta; Katagiri, Hideki
Abstract : We experienced a case with insulin allergy which manifested soon after COVID‐19 vaccination.